1
$\begingroup$

Prolem: ${\mathop {\lim }\limits_{x \to {\pi ^ - }} \mathop {\lim }\limits_{n \to \infty } \left( {{n^2}\left( {1 - \sin \frac{\pi }{{2n}} \cdot \sum\limits_{k = 1}^{n - 1} {\sin \left( {\frac{{\left( {2\left\lfloor {\sqrt {kn} } \right\rfloor + 1} \right)\pi }}{{2n}}} \right)} } \right)\left( {\frac{1}{{4{{\cos }^2}\frac{x}{2}}} - \sum\limits_{n = 1}^\infty {\frac{{n\cosh \left( {nx} \right)}}{{\sinh \left( {n\pi } \right)}}} - \frac{1}{{12}}} \right)} \right)}$,

where $\lfloor\cdot\rfloor$ is greatest integer function.

Add: In my opinion, we must solve $$\mathop {\lim }\limits_{n \to \infty } {n^2}\left( {1 - \sin \frac{\pi }{{2n}} \cdot \sum\limits_{k = 1}^{n - 1} {\sin \left( {\frac{{\left( {2\left\lfloor {\sqrt {kn} } \right\rfloor + 1} \right)\pi }}{{2n}}} \right)} } \right)$$ and $$\mathop {\lim }\limits_{x \to {\pi ^ - }} \left( {\frac{1}{{4{{\cos }^2}\frac{x}{2}}} - \sum\limits_{n = 1}^\infty {\frac{{n\cosh \left( {nx} \right)}}{{\sinh \left( {n\pi } \right)}}} - \frac{1}{{12}}} \right).$$ But how can we obtain them?

And in this, we have $$\sum\limits_{k = 1}^{n - 1} {\sin \left( {\frac{{\left( {2\left\lfloor {\sqrt {kn} } \right\rfloor + 1} \right)\pi }}{{2n}}} \right)} = \cot \left( {\frac{\pi }{{2n}}} \right)\cos \left( {\frac{\pi }{{2n}}} \right).$$ So we have \begin{align*} &\mathop {\lim }\limits_{n \to \infty } {n^2}\left( {1 - \sin \frac{\pi }{{2n}} \cdot \sum\limits_{k = 1}^{n - 1} {\sin \left( {\frac{{\left( {2\left\lfloor {\sqrt {kn} } \right\rfloor + 1} \right)\pi }}{{2n}}} \right)} } \right) \\ =& \mathop {\lim }\limits_{n \to \infty } {n^2}\left( {1 - \sin \frac{\pi }{{2n}} \cdot \cot \left( {\frac{\pi }{{2n}}} \right)\cos \left( {\frac{\pi }{{2n}}} \right)} \right)\\ = &\mathop {\lim }\limits_{n \to \infty } {n^2}\left( {1 - {{\cos }^2}\left( {\frac{\pi }{{2n}}} \right)} \right) = \mathop {\lim }\limits_{n \to \infty } {n^2}{\sin ^2}\left( {\frac{\pi }{{2n}}} \right) = \frac{{{\pi ^2}}}{4} \end{align*}

What about the next one? How to solve it?

$\endgroup$
0
$\begingroup$

Let $$f(x)=\sum_{n=1}^{\infty}\dfrac{\sinh{(nx)}}{\sinh{(n\pi)}}$$ so $$f'(x)=\sum_{n=1}^{+\infty}\dfrac{n\cosh{(nx)}}{\sinh{(n\pi)}}$$ and other hand $$f(x)=\dfrac{1}{e^{\pi-x}-1}+\sum_{n=1}^{\infty}\dfrac{e^{-(\pi-x)n}(e^{-2n\pi}-e^{-2n\pi})}{1-e^{-2n\pi}}$$ so $$f'(x)=\dfrac{e^{\pi-x}}{(e^{\pi-x}-1)^2}+\sum_{n=1}^{\infty}\dfrac{ne^{-(\pi-x)n}(e^{-2n\pi}-e^{2nx})+2ne^{-(\pi-x)n}e^{-2nx}}{1-e^{-2n\pi}}$$ and it not easy to prove $$\lim_{x\to \pi^{-}}\sum_{n=1}^{\infty}\dfrac{ne^{-(\pi-x)n}(e^{-2n\pi}-e^{2nx})+2ne^{-(\pi-x)n}e^{-2nx}}{1-e^{-2n\pi}}=2\sum_{n=1}^{\infty}\dfrac{n}{e^{2n\pi}-1}=\dfrac{1}{12}-\dfrac{1}{4\pi}$$ so you can prove by done

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.